Home Production of Childcare and Labour Supply Decisions in a Collective Household Model - Hélène Turon (Institute of Labor Economics (IZA), 2019)
This paper proposes a dynamic structural model of labour market and childcare choices for couples within a collective model of decision making. We formalise explicitly the need for childcare as a function of the age structure of the children population in the household then examine the determinants of the decision to supply labour. The fraction of home-produced childcare to household childcare needs is considered to be a public good within the household, for which preferences are heterogeneous across households. An important feature of our framework, which introduces one of the dynamic dimensions of the decision, is that we take into account the implications of today's labour supply decision on future wage growth and future bargaining power. The decision to leave (partially or not) the labour market is often taken within a couple but, in the event of divorce, the impact of this decision may not be borne by both parties equally, which may render the initial decision inefficient. Using data from the BHPS, we then present a structural estimation of our model to quantify these various components of the choice of home childcare vs. labour supply. We are able to quantify each household's sensitivity to potential childcare policies and find that a large part of the dispersion in these responses comes from households' valuation of home-produced childcare.
Keywords: J12; J13; J22; J31; J38; 330; household; labour supply; collective model; childcare; commitment